The role of Art, Spiritual, Science, Engineering & Technology (ASSET) for Improving Quality of the Indonesian Human Resources (IQIHR) - Rohani Jahja Widodo (Semantik, 2011)
This paper presents the role of Art, Spiritual, Science, Engineering & Technology (ASSET) for Improving the Quality of the Indonesian Human Resources (IQIHR). There are four universe aspects: Physical, Intellectual, Emotional and Spiritual (PIES) aspects related with IQIHR. There are three basic requirements for improving PIES aspects : Material, Energy and Information (MEI). Those aspects are important inputs for Education & Training (E&T) and Research & Development (R&D) activities for development of ASSET. IQIHR is desired output that must be attained from activities of E&T and R&Dbased on ASSET.Keywords: ASSET, IQIHR, PIES, MEI, E&T, R&D.